Digitization, Commodification, Criminalization: The Evolution of Criminal Copyright Infringement and the Importance of the Willfulness Requirement - Lydia Pallas Loren (Washington University Law Quarterly, 1999)
Part I of this Article examines the historical evolution of criminal copyright infringement in this country, culminating in the adoption of the NET Act. Part I also provides an overview of the changes in criminal copyright infringement affected by the NET Act. Part II analyzes why, after 100 years, Congress eliminated the requirement of a profit motive for criminal liability and significantly expanded the reach of the criminal sanctions of the Copyright Act. Part II also describes not just the decisional impetus for the amendment to the Copyright Act, United States v. LaMacchia, but the underlying pressures placed on copyright law by the digitization of copyrighted works and the commodification of the intangible rights granted by copyright law. Part III explores the possible reach of this new Act, questioning whether it casts the net of criminal infringement too wide. Finally, Part IV addresses the importance of the element of willfulness retained in the statute. This section discusses the interpretation of the term “willful” by the Supreme Court in other areas of law and the interpretation that term has been given by lower courts in the context of the Copyright Act. This section proposes that to prove criminal copyright infringement the government should be required to show that the defendant intentionally violated a known legal duty and that the defendant lacked a good faith belief that the conduct at issue was lawful. Only with this standard in place can the NET Act be kept within reasonable bounds and not risk deterring the lawful and socially productive activity which underlying policies of the Copyright Act seek to encourage.
Keywords: Copyright infringement; Commercial crimes; Criminal intent; Criminal law; No Electronic Theft Act of 1997